2021
DOI: 10.1093/plcell/koab164
|View full text |Cite|
|
Sign up to set email alerts
|

VPS18-regulated vesicle trafficking controls the secretion of pectin and its modifying enzyme during pollen tube growth in Arabidopsis

Abstract: In eukaryotes, homotypic fusion and vacuolar protein sorting (HOPS) as well as class C core vacuole/endosome tethering (CORVET) are evolutionarily conserved membrane tethering complexes that play important roles in lysosomal/vacuolar trafficking. Whether HOPS and CORVET control endomembrane trafficking in pollen tubes, the fastest growing plant cells, remains largely elusive. In this study, we demonstrate that the four core components shared by the two complexes, Vacuole protein sorting 11 (VPS11), VPS16, VPS3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…In the other strategy, gametophytes carrying the mutated gene are distinguished by fluorescence labels. This approach has been employed to successfully separate and collect mutant pollen of vacuolar protein sorting‐associated protein 41 (VPS41) and VPS18, two essential proteins involved in endomembrane trafficking (Hao et al, 2016; Zhong et al, 2020; Hou et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the other strategy, gametophytes carrying the mutated gene are distinguished by fluorescence labels. This approach has been employed to successfully separate and collect mutant pollen of vacuolar protein sorting‐associated protein 41 (VPS41) and VPS18, two essential proteins involved in endomembrane trafficking (Hao et al, 2016; Zhong et al, 2020; Hou et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The process underlying the polar distribution of proteins depends on the establishment and maintenance of directional transport. The endomembrane system is needed for the directional transport of proteins to specific sites, the strong accumulation of proteins, and further recycling by endocytosis and redistribution between the trans-Golgi network/endosome and plasma membrane ( Yang et al, 2020 ; Dubois and Jaillais, 2021 ; Hou et al, 2021 ; Ruan et al, 2021 ). Phospholipid transport catalyzed by P4-ATPase plays an important role in vesicle transport.…”
Section: Discussionmentioning
confidence: 99%
“…Transient expression of AtPMEI2 in tobacco promoted pollen tube growth while that of PME did the opposite [84]. VAN-GUARD1 (VGD1) and AtPPME1 are two pectin methylesterase, whose functional loss or mistargeting resulted in defective pectin network and abnormal pollen tube growth [85][86][87]. In addition to pectin, cellulose also is an important part of the pollen tube wall.…”
Section: Pm-targeted Vesicular Traffickingmentioning
confidence: 99%
“…Recent studies indicated an essential role of these tethering complexes in pollen tube growth. Functional loss of Arabidopsis Vps41 resulted in failed style penetration of pollen tubes [114] and that of Vps11, Vps16, and Vps18 substantially compromised this process [31,87,115]. Defective pollen tube growth due to mutations of the tethering complexes is not only associated with abnormal vacuolar morphology and vesicle-tonoplast fusion but often with abnormal deposition of cell wall components [87].…”
Section: Vacuolar Traffickingmentioning
confidence: 99%
See 1 more Smart Citation